The Effect of Corporate Governance and Corporate Social Responsibility on Tax Avoidance in Manufacturing Companies Listed on the IDX - Ibrahim, Ibrahim; Abbas, Muchlis; Amril, Amril; Syamsuri, Helmy; Syarifuddin, Syarifuddin (International Journal of Artificial Intelligence Research, 2023)
This study was conducted with the aim of: (1) examine the effect of the proportion of independent commissioners on tax avoidance; (2) examine the effect of audit quality on tax avoidance; (3) examine the effect of institutional ownership on tax avoidance; (4) examine the effect of managerial ownership on tax avoidance; (5) examine the effect of CSR disclosure on tax avoidance. The type of data used in this study is secondary data taken from manufacturing company reports from 2015-2018. The data is obtained from the Indonesia Stock Exchange which can be accessed on the official website of the Indonesia Stock Exchange (www.idx.co.id) as well as the company website of the related company. The data collection technique used is the documentation method. The data analysis method used is multiple linear regression analysis. The results of this study indicate that: (1) ownership of the proportion of independent commissioners has a negative and significant effect on tax avoidance; (2) audit quality has a negative and significant effect on tax avoidance; (3) institutional ownership has a negative and significant effect on tax avoidance; (4) managerial ownership has a negative and significant effect on tax avoidance; (5) CSR has a negative and significant effect on tax avoidance.